Dynamic modeling and performance of compliant mechanisms with inflection beams. (April 2019) - Yu, Yue-Qing; Zhang, Na
Highlights: The 5R dynamic pseudo-rigid-body model (5R D-PRBM) is proposed for compliant mechanisms with inflection beams. The dynamic equation of the 5R D-PRBM is derived based on Lagrangian equation. Numerical studies on the dynamic performance of inflection beam are presented comparing ADAMS. An example of compliant parallel-guiding mechanism is presented using the 5R D-PRBM. Abstract: A study on the dynamic modeling and performance for compliant mechanisms with inflection beams is presented. Based on the pseudo-rigid-body model (PRBM), a 5R Dynamic PRBM (5R D-PRBM) is proposed for the flexural beams with inflection points. The dynamic equation of the 5R D-PRBM is derived using Lagrangian equation. Numerical investigations on the dynamic responses of the flexural beam with an inflection point are presented by the 5R D-PRBM. The advantage of the new model is illustrated comparing with ADAMS simulation. An example of compliant parallel-guiding mechanism is presented using the 5R D-PRBM.